A systematic review of the literature on counselling and psychotherapy for the prevention of suicide: 1. Quantitative outcome and process studies. Issue 3 (16th August 2013) - Winter, David; Bradshaw, Siobhan; Bunn, Frances; Wellsted, David
Abstract: Scope of review: The paper reports a meta‐review of 15 previous systematic reviews and meta‐analyses of the literature concerning the outcome of counselling and psychotherapy with people at risk of suicide; a meta‐analysis of 67 outcome studies in this area; and a narrative review of 17 studies of the therapeutic process. Publication time span: The literature reviewed was published between 1981 and 2008. Publication origin: The majority of the literature reviewed was by authors from the USA or the UK, but there were also authors from other European countries, Australia, Canada, India, and Sri Lanka. Findings: There is evidence of the effectiveness of dialectical behaviour therapy, cognitive‐behavioural therapy, and problem solving therapy, but also for other forms of therapy. Therapist and client variables, as well as the therapeutic relationship, appear to be related to treatment outcome. Conclusions: People at risk of suicide should have access to psychological interventions, including, but not necessarily limited to, those within the cognitive‐behavioural spectrum. Therapies for which there have been promising findings, but which are under‐researched, should be a research priority.